On the Public Danger of Payment Fraud - Timofey I. Mitrofanov (Сибирское юридическое обозрение, 2016)
The article examines the changes and additions to the Criminal Code of the Russian Federation, which caused establishing of special rules on liability for fraud, including payment fraud. The author examines the social danger of payment fraud, compares sanctions of the general norm on fraud (Art. 159 of the Criminal Code of the Russian Federation) and Art. 159.2 of the Criminal Code of the Russian Federation.